2012
DOI: 10.1002/smll.201200639
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Toxicity of Hydroxyapatite Nanoparticles in Catfish Cells and Zebrafish Embryos

Abstract: The toxicity of needle-(nHA-ND) and rod-shaped (nHA-RD) hydroxyapatite (HA) nanoparticles is evaluated in vitro on catfish B-cells (3B11) and catfish T-cells (28s.3) and in vivo on zebrafish embryos to determine if biological effects are similar to the effects seen in mammalian in vitro systems. Neither nHA-ND nor nHA-RD affect cell viability at concentrations of 10 to 300 μg mL(-1) . However, 30 μg mL(-1) needle-shaped nHA lower metabolic activity of the cells. Axial deformations are seen in zebrafish exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…In addition, Pal et al (2007) found that truncated triangular Ag NPs inhibited bacteria (E. coli) more effectively than Ag nano-spheres or nano-rods. Furthermore, needleshaped hydroxyapatite was found to delay embryo hatching in zebrafish more than rod-shaped hydroxyapatite after 72 h (Zhao et al, 2012). Differences in toxicity among ENPs with different shapes might be a result of differences in bioaccumulation, differences in reactivity, or both, and teasing apart these differences is necessary for sound risk assessments.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, Pal et al (2007) found that truncated triangular Ag NPs inhibited bacteria (E. coli) more effectively than Ag nano-spheres or nano-rods. Furthermore, needleshaped hydroxyapatite was found to delay embryo hatching in zebrafish more than rod-shaped hydroxyapatite after 72 h (Zhao et al, 2012). Differences in toxicity among ENPs with different shapes might be a result of differences in bioaccumulation, differences in reactivity, or both, and teasing apart these differences is necessary for sound risk assessments.…”
Section: Introductionmentioning
confidence: 98%
“…When exposed to the embryos, the dot particles may translocate through the chorionic pores of the zebrafish and get trapped within the chorionic space. NPs trapped in the chorion can restrict the diffusion of nutrients and oxygen supply to the embryo, causing axial deformities in the tail and spine as well as edema [25,26,27]. The accumulated nanoparticles can also alter the charge, diffusion, and interactions of chorionic proteins such as the hatching enzyme and membrane transporter, leading to interference in the signaling cascades of embryonic development [25,28].…”
Section: Resultsmentioning
confidence: 99%
“…Such apoptotic effects observedin HepG2 cells were the basis for proposing HA as utilizable in the treatment of hepatoma and other types of cancer [62]. Needle-shaped HA also slowed down the cell metabolism and inhibited hatching in catfish T-cells and zebrafish embryos in a dose-dependent manner [63]. Other studies suggested good biocompatibility and a lack of cytotoxic effects of needle-shaped HA when tested in vitro [64,65], demonstrating a great degree of variability of the biological response to such morphologies.…”
Section: Resultsmentioning
confidence: 99%